Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1002/pssa.201127336
|View full text |Cite
|
Sign up to set email alerts
|

Improving open‐circuit voltage in DSSCs using Cu‐doped TiO2 as a semiconductor

Abstract: TiO2 doping has been widely used in photocatalysis and photovoltaic cells to improve the performance of this semiconductor. This paper studies the use of copper as a dopant in TiO2 in dye‐sensitized solar cells (DSSC), analysing the effect on the photovoltaic properties of the cells of different concentrations of copper incorporated into the semiconductor. The copper‐doped TiO2 semiconductor was characterized with several instrumental techniques, including X‐ray diffraction (XRD), inductively coupled plasma at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 45 publications
2
42
0
Order By: Relevance
“…Doping deteriorates the efficiency of DSSCs made by amorphous TiO 2 powders. Structural analysis showed that (Mn, Co and Cu) doping anatase TiO 2 powders [19] and they explained this decline by the charge recombination which occured related to trap density of TiO 2 electrodes with (Co and Cu) ions doping. The increase of V oc with Co and Cu doping is caused by the increase of the structural disorder that promotes the extension of the space charge region in the semiconductor due to the decrease of oxygen vacancy concentration at the TiO 2 surface [40].…”
Section: Uv-vis Spectroscopymentioning
confidence: 97%
See 1 more Smart Citation
“…Doping deteriorates the efficiency of DSSCs made by amorphous TiO 2 powders. Structural analysis showed that (Mn, Co and Cu) doping anatase TiO 2 powders [19] and they explained this decline by the charge recombination which occured related to trap density of TiO 2 electrodes with (Co and Cu) ions doping. The increase of V oc with Co and Cu doping is caused by the increase of the structural disorder that promotes the extension of the space charge region in the semiconductor due to the decrease of oxygen vacancy concentration at the TiO 2 surface [40].…”
Section: Uv-vis Spectroscopymentioning
confidence: 97%
“…On the other hand, they illustrate that lower efficiency values were obtained for Mn-doped TiO 2 (1.85%) and Co-doped TiO 2 (1.06%). In fact, Navas et al [19] showed that the presence of copper as a dopant in TiO 2 , in DSSCs made with a standard configuration, leads to an improvement up to 10% in the open-circuit voltage of DSSCs.…”
Section: Introductionmentioning
confidence: 97%
“…Although the study of Fe doped TiO 2 is well documented, limited spectroscopic data has been reported. Sn [16,37] and Cu [38] doped TiO 2 have been used as effective oxide layers with significant enhancement in charge transport for DSSC applications but with limited study on charge decay kinetics. Duan et al [16] obtained a photoelectric conversion efficiency enhancement of 12.0 % over pure TiO 2 with Sn doped TiO 2 electrodes.…”
Section: Page 6 Of 53mentioning
confidence: 99%
“…The results showed that the open circuit voltage (V oc ) of Cu doped TiO 2 electrode enhances significantly. However, in that case, the cell efficiency of doped TiO 2 was shown to be lesser than that of pure TiO 2 [33]. Keeping these in view, in the present work, we report convenient preparation strategy for Ti (1Àx) Cu x O 2 (x ¼ 0.00.…”
Section: Introductionmentioning
confidence: 72%